INTEGRAL HENSTOCK-STIELTJES FUNGSI BERNILAI VEKTOR - Umi Mahnuna Hanung; Ch. Rini Indrati (PYTHAGORAS Jurnal Pendidikan Matematika, 2009)
This paper discusses about the generalization of the Henstock-Stieltjes integral for vector-valued functions which are defined on a closed interval [a,b]R. The generalization has been done up to the existance of this integral.Key words: Henstock-Stieltjes integral, vector-valued function and bounded function.